2021
DOI: 10.1055/s-0040-1722679
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment and Functional Classification in Children with Cerebral Palsy

Abstract: Background Cerebral palsy (CP) is the most common motor impairment in childhood and often accompanied by a broad spectrum of comorbidities. Data are sparse concerning visual impairment (VI) and functional classification among CP children. Objective The objective of this study was to analyze the prevalence of VI among children with CP and to investigate a possible association between VI and Gross Motor Function Classification System (GMFCS) and the Bimanual Fine Motor Function (BFMF). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this context, multisensory stimulation interventions may improve sensory and motor function ( 2 ). A systematic literature review found that visual-perceptual impairment ranged from 40% to 50% in children with CP ( 3 ), as also confirmed by Rauchenzauner et al ( 4 ), who found visual-perceptual impairment in 59.5% of them. Novak also reports that 4% of children with CP have severe hearing problems or are deaf ( 5 ).…”
Section: Introductionsupporting
confidence: 63%
“…In this context, multisensory stimulation interventions may improve sensory and motor function ( 2 ). A systematic literature review found that visual-perceptual impairment ranged from 40% to 50% in children with CP ( 3 ), as also confirmed by Rauchenzauner et al ( 4 ), who found visual-perceptual impairment in 59.5% of them. Novak also reports that 4% of children with CP have severe hearing problems or are deaf ( 5 ).…”
Section: Introductionsupporting
confidence: 63%
“…In addition, cases with moderate mental retardation had higher index of surface variance, index of vertical asymmetry, index of height asymmetry, and index of height decentration than those with mild mental retardation. Other ocular problems such as vision disorders, strabismus and retinal problems have already received attention in these children 6 , 21 , 22 . Our finding indicates the necessity of more attention to CP children and children with more severe mental retardation in terms of keratoconus indicators 23 .…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded reviews only, case studies, abstracts at meetings when later published as a peer-reviewed paper, and papers focused on surgical outcomes. We included 54 studies on Caucasians (most of them in Europe, North America and Australia), 9,10,14,3642,44,48–53,64101 11 studies from the Middle East, 5,16,23,102109 9 on Hispanics (most of them from Latin America), 15,110117 41 from East Asia, 12,13,43,46,56,58,118–152 23 from South Asia, 33,35,45,47,54,57,153–169 and 5 from Africa 11,170174 (Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…3,5,37,38,45,46,48,58,70,115,153,159,[198][199][200][201][202] Relatively few authors disagree with this conclusion. 39,74,101 Some authors noted that strabismus is most frequent in spastic tetraplegia (or triplegia) and somewhat less in diplegia, still less in hemiplegia, and rare in athetoid or ataxic CP, 5,11,36,39,40,45,47,64,70,101,105,149,163 while others disagree with this notion. 15,[41][42][43]52,56,67,78,100,111,203 Authors concur that there is no association between the type of strabismus (esotropia, exotropia, hypertropia) and the type of CP.…”
Section: Is Strabismus Prevalence Associated With Cp Types?mentioning
confidence: 99%